Buchbesprechung: Brixa, Anna: Der ›dunkle‹ Kempowski. Kempowski anders lesen. München. Belleville 2025 (Theorie und Praxis der Interpretation 13) - Elit, Stefan (Kempowski-Jahrbuch)

4th Symposium on Algorithmic Foundations of Dynamic Networks.

Direct assessment of the influence of pose repeatability on the accuracy of dimensional measurements for computed tomography systems with high degrees of freedom - Butzhammer, Lorenz; Handke, Niklas; Wittl, Simon; Herl, Gabriel; Hausotte, Tino (Measurement Science and Technology)
Abstract Industrial x-ray computed tomography (CT) systems with high geometric flexibility are increasingly utilized for large-scale measurement objects or challenging measurement tasks. To maintain high accuracy when deviating from the established circular scan trajectory, trajectory calibration methods using multi-sphere reference objects with known marker positions are commonly employed. These multi-sphere objects can either be scanned together with the measurement object (online trajectory calibration) or in a separate scan (offline trajectory calibration). While offline calibration increases machine time, it generally results in higher scan quality. However, a sufficient pose repeatability is necessary to ensure comparable or even superior accuracy to online calibration. In this contribution, we present a straightforward procedure to compare both types of trajectory calibration in a way that the differences of the results can directly be traced back to the influence of the pose repeatability. The multi-sphere reference object is not only used for trajectory calibration, but simultaneously as a measurement object for repeated measurements. The methodology is tested on both a twin robotic CT system and a conventional CT system that is additionally equipped with a hexapod manipulator for adaptive object tilting. Results showed, independent from the type of trajectory calibration, systematic measurement errors in the order of 10 −5 –10 −4 of measured sphere distances and sphericity values below 50 μ m . For sphere distances, random errors were increased by a factor of 5 due to the offline trajectory calibration, but were still low ( < 1 μ m ) in comparison to systematic errors and the spread of different measurement features. Overall, both investigated systems demonstrated sufficient positioning repeatability for offline trajectory calibration. The method is in general also applicable to any other types of manipulator systems used for CT devices. It provides a workflow for the decision which type of trajectory calibration is preferable for a given CT system.

Thermal Behavior of n-Octanol and Related Ether Alcohols - Hoffmann, Markus M.; Gutmann, Torsten; Buntkowsky, Gerd (Journal of Chemical & Engineering Data)
The thermal behavior of n-octanol and related ether alcohols has been studied by differential scanning calorimetry (DSC). The melting point, heat of fusion, and isobaric heat capacities of n-octanol obtained from the DSC measurements are in good agreement with literature values. The ether alcohols display kinetic barriers for forming a solid phase during cooldown. These barriers are least for 6-methoxyhexanol that forms a solid upon cooling except for the highest measured temperature change rate of 40 K·min–1, followed by 4-propoxybutanol that forms a solid during cooldown only at low cooling rates. 2-Pentoxyethanol and 5-ethoxypentanol form a solid during the heating cycle that then melts again upon further heating. 3-Butoxypropanol does not display any exo- and endothermic features for all measured temperature change rates. Consequently, new data on melting point and heats of fusion are reported for the ether alcohols except for 3-butoxypropanol. New isobaric heat capacities are presented as well for the liquid phase of these ether alcohols. The thermal behavior of n-octanol and related ether alcohols has been studied by differential scanning calorimetry (DSC). The melting point, heat of fusion, and isobaric heat capacities of n-octanol obtained from the DSC measurements are in good agreement with literature values. The ether alcohols display kinetic barriers for forming a solid phase during cooldown. These barriers are least for 6-methoxyhexanol that forms a solid upon cooling except for the highest measured temperature change rate of 40 K·min–1, followed by 4-propoxybutanol that forms a solid during cooldown only at low cooling rates. 2-Pentoxyethanol and 5-ethoxypentanol form a solid during the heating cycle that then melts again upon further heating. 3-Butoxypropanol does not display any exo- and endothermic features for all measured temperature change rates. Consequently, new data on melting point and heats of fusion are reported for the ether alcohols except for 3-butoxypropanol. New isobaric heat capacities are presented as well for the liquid phase of these ether alcohols.

Influence of dispersion gas flow on the spray characteristics and γ-Fe2O3 nanoparticles formation and properties in reference SpraySyn burners - Massopo, Orlando; Tischendorf, Ricardo; Gonchikzhapov, Munko; Kasper, Tina; Augustin, Peter; Özer, Burak; Reddemann, Manuel; Kneer, Reinhold; Sheikh, Mohammed-Ali; Mert, Aydan Akyildiz; Wiggers, Hartmut; Schmid, Hans-Joachim (Powder Technology)
This study investigates the effect of dispersion gas (DG) flow on the formation and properties of maghemite (γ-Fe2O3) nanoparticles using standardized SpraySyn burners (SS1 and SS2). Several diagnostics were employed to characterize the spray and nanoparticles. Increasing DG flow (6 - 12 slm) results in smaller droplet sizes (DS), cooler flame temperatures, shorter high-temperature droplet/particle residence times, and smaller agglomerates in the size range of 5 - 12 nm with narrower primary particle size distribution, corresponding to higher mass fractal dimensions, as supported by TEM and SMPS analysis, resulting in more compact agglomerates. BET and TEM confirmed decreasing primary particle sizes with increasing DG flow. Raman and XRD analyses predominantly identified maghemite, which shows a bimodal distribution of crystallite sizes, while SS1 samples have a greater proportion of larger crystallites. The self-preserving size distributions of agglomerates with a geometric standard deviation of 1.5 are reached faster with increasing DG flow. The barrier effect of DG observed in SS1 leads to slower droplet combustion kinetics, higher temperatures, and delayed precursor release, which, along with downstream flow recirculation, result in significantly higher agglomeration rates outside the visible flame. SS2 demonstrates improved atomization, more stable flames, and finer, uniform nanoparticles with less carbonaceous residues (CR). Conversely, SS1 showed broader DS distributions and higher CR levels on the γ-Fe2O3 surface, especially at higher DG flow. This work highlights the essential role of DG flow and nozzle geometry in controlling droplet evaporation, flame stability, and nanoparticle growth, offering insights for optimizing SFS and validating numerical models.
Keywords: Spray flame synthesis; iron oxide nanoparticle; SpraySyn burner; Dispersion gas; Coaxial atomization; HiaT-SMPS

Bolted Langevin transducers with leadfree piezoelectric ceramics - Scheidemann, Claus; Bornmann, Peter; Littmann, Walter; Hemsel, Tobias
Lead-containing piezoelectric ceramics are still the base for today’s ultrasonic transducers used in broad applications. This is partly due to missing powerful lead-free piezoelectric ceramic parts in the commercial market. There has been much research on lead-free materials but developing them into marketable parts seems to be an ongoing process. The actual exemption of ROHS has expired, but as the new exemption has already been requested, ceramic suppliers keep on selling lead containing products. Nevertheless, these should be replaced by lead-free alternatives for environmental and health issues. This contribution focuses on exploring the technological readiness level of lead-free hard piezoceramics for prestressed ultrasonic transducers. A small series of bolted Langevin transducers was set up with standard PZT material and three commercial lead-free variants. Results of the building process from individual ring ceramic characteristics to transducer load tests are presented. The main finding of this study is that the lead-free materials technically can compete with the standard PZT for medium-power applications. Some adaptations in the ultrasonic system must be done: the geometry must be altered to fit resonance frequency, and higher voltages or thinner ceramics are needed to achieve the same vibration level at low load. For reaching same power, the volume of lead-free ceramics must be 1.5 to 3 times larger. As already promoted in literature, mechanical losses at high vibration levels are smaller for the lead-free materials. This might help to argument lead-free piezoelectric materials in some applications. References 1. Directive 2011/65/EU of the European Parliament and of the Council of 8 June 2011 on the Restriction of the Use of Certain Hazardous Substances in Electrical and Electronic Equipment. EUR-Lex Document 02011L0065-20240801. Available online: http://data.europa.eu/eli/dir/2011/65/2024-08-01 (accessed on 24 January 2025). 2. Langevin, P. (1918) Method and Apparatus for Transmitting and Receiving Submarine Elastic Waves Using the Piezoelectric Properties of Quartz. French Patent Office; Patent No. FR505703. 3. Hemsel, T.; Twiefel, J. (2023) Piezoelectric Ultrasonic Power Transducers. In Encyclopedia of Materials: Electronics; Academic Press: Oxford, UK; pp. 276–285. https://doi.org/10.1016/b978-0-12-819728-8.00047-4. 4. ATHENA Technologie Beratung GmbH (2025) Description of Ultrasound Generator. Available online: http://shop.myathena.de/epages/12074748.sf/de_DE/?ObjectPath=/Shops/12074748/Products/AM200 (accessed on 13 January 2025). 5. Littmann, W.; Hemsel, T.; Kauczor, C.; Wallaschek, J.; Sinha, W. (2003) Load-adaptive phase-controller for resonant driven piezoelectric devices. Proc. World Congr. Ultrason. 2003, 48, 547–550. 6. Scheidemann, C., Bornmann, P., Littmann, W., & Hemsel, T. (2025). Lead-Free Ceramics in Prestressed Ultrasonic Transducers. Actuators, 14(2), 55. https://doi.org/10.3390/act14020055
Keywords: lead free piezoelectric ceramics; bolted Langevin transducer; medium power ultrasound.

Grammatik in der Schule. Eine Einführung - Becker, Tabea; Peschel, Corinna; Topalović, Elvira
Die Rolle der Grammatik im Deutschunterricht wird in der sprachdidaktischen Forschung intensiv diskutiert. Diese Einführung führt die Diskussion konstruktiv fort: Der Band bietet einen erweiterten, oft innovativen Blick auf grammatisches Lernen im Primar- und Sekundarbereich, er thematisiert neben den Grundlagen des Grammatikerwerbs auch Sprach(en)bewusstheit und Mehrsprachigkeit. Gemäß den aktuellen Bildungsstandards für das Fach Deutsch fokussiert er formale und funktionale Aspekte von Grammatik. Der Praxisteil liefert Methoden und Konzepte der Vermittlung als Best-Practice-Beispiele – nicht nur für Lehramtsstudierende, sondern auch für praktizierende Deutschlehrkräfte.
Keywords: Grammatik; Deutsch; Schule

Das ‚andere‘ Europa der Schriftsteller. Ideen, Netzwerke und Schreibweisen des antiliberalen Europa-Diskurses in Deutschland und Österreich (1918–1934) - Heise, Tillmann

„Alles was gut ist“ – Jan Wagners lyrische Speisen (mit Getränken) - Elit, Stefan (Was im Gedicht geschieht: Jan Wagner. Paderborn Wintersemester 2023/2024)

Monitoring phage infection and lysis of surface-immobilized bacteria by QCM-D - Pothineni, Bhanu K.; Probst, René; Kiefer, Dorothee; Dobretzberger, Verena; Barišić, Ivan; Grundmeier, Guido; Keller, Adrian (Analytical and Bioanalytical Chemistry)
Abstract While being a promising approach for the treatment of infections caused by drug-resistant, pathogenic bacteria, the clinical implementation of phage therapy still faces several challenges. One of these challenges lies in the high strain-specificity of most bacteriophages, which makes it necessary to screen large phage collections against the target pathogens in order to identify suitable candidates for the formulations of personalized therapeutic phage cocktails. In this work, we evaluate the potential of quartz crystal microbalance with dissipation monitoring (QCM-D) to identify and detect phage infection and subsequent lysis of bacteria immobilized on the surfaces of the QCM-D sensors. Using lytic Escherichia coli phage T7 as a model, we show that phage infection of E. coli cells results in various unique alterations in the behaviors of the frequency (Δ f ) and dissipation (Δ D ) signals, which are not observed during exposure of the E. coli strain to non-infectious Bacillus subtilis phage phi29 at similar concentration. To aid future phage screening campaigns, we furthermore identify a single measurement parameter, i.e., the spread between the different overtones of Δ D , that can be used to detect phage-induced lysis. For T7 infection of E. coli , this is achieved within 4 h after inoculation, including immobilization and growth of the bacteria on the sensor surface, as well as the completed phage propagation cycle. Given the commercial availability of highly automated multichannel systems and the fact that this approach does not require any sensor modifications, QCM-D has the potential to become a valuable tool for screening medium-sized phage collections against target pathogens. Graphical Abstract

Dynamic modulations of effective brain connectivity associated with postural instability during multi-joint compound movement on compliant surface - Lehmann, Tim; Visser, Anton Samuel; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Experimental Brain Research)
Abstract Random fluctuations in somatosensory signals affect the ability of effectively coordinating multimodal information pertaining to the postural state during movement. Therefore, this study aimed to investigate the impact of a compliant surface on cortico-cortical causal information flow during multi-joint compound movements. Fifteen healthy adults (7 female / 8 male, 25.9 ± 4.0 years) performed 5 × 20 repetitions of bodyweight squats on firm and compliant surface. Motor behavior was quantified by center of pressure (CoP) displacements, hip movement and the root mean square of the rectus femoris activity. Using source space analysis, renormalized partial directed coherence (rPDC) computed subject-level multivariate effective brain connectivity of sensorimotor nodes. Bootstrap statistics revealed significantly decreased medio-lateral CoP displacement ( p < 0.001), significantly increased velocity of medio-lateral hip motion ( p < 0.001) as well as significantly lower rectus femoris activity ( p < 0.01) in the compliant surface condition. On the cortical level, rPDC showed significantly modulated information flow in theta and beta frequencies for fronto-parietal edges ( p < 0.01) only during the concentric phase of the movement. The compliant surface led to increased difficulties controlling hip but not center of pressure motion in the medio-lateral plane. Moreover, a decreased activation of the prime movers accompanied by modulations of effective brain connectivity among fronto-central nodes may point to altered demands on sensorimotor information processing in presence of sensory noise when performing bodyweight squats on compliant surface. Further studies are needed to evaluate a potential benefit for athletic and clinical populations.

Paradigmenwechsel und Metapher. Ein Weg zur Gesellschaft der Nachhaltigkeit? - Albus, Vanessa (Nachhaltigkeit in der Medienkommunikation. Ethische Anforderungen und praktische Lösungsansätze)

Unveiling the Distinctions: Computer Versus Sport-Specific Neurocognitive Tests - Gondwe, Benedict; Heuvelmans, Pieter; Benjaminse, Anne; Büchel, Daniel; Baumeister, Jochen; Gokeler, Alli (Journal of Sport Rehabilitation)
Context : Traditional assessments of high-order neurocognitive functions are conducted using pen and paper or computer-based tests; this neglects the complex motor actions athletes have to make in team ball sports. Previous research has not explored the combination of neurocognitive functions and motor demands through complex tasks for team ball sport athletes. The primary aim of the present study was to determine the construct validity of agility-based neurocognitive tests of working memory (WM) and inhibition. Methods : Twenty-seven athletes (5 females; mean age 24.2 [4.7] y; height 183.6 [9.1] cm; body mass 77.5 [11.2] kg) participated in the construct validity assessments that included computer-based tests (working memory capacity and stop-signal reaction time) and sport-specific assessments performed on the SpeedCourt system. Results : Construct validity analysis of sport-specific working memory yielded acceptable construct validity ( r = .465, P < .05), whereas the sport-specific stop-signal task resulted in low construct validity ( r = .179, P > .05). The poor construct validity results highlight the large variance between computer-based and sport-specific neurocognitive assessments. Conclusion : Sport-specific assessments are more complex and include more degrees of freedom potentially due to athletes’ center of mass displacement during task execution. These findings suggest that future research should focus more on the development of sport-specific assessments. These should include the cognitive and motor demands encountered during practice and competition, not use computer-based/pen and paper assessments for return to play decisions.

Vision: Towards True User-Centric Design for Digital Identity Wallets - Last, Yorick; Arias Cabarcos, Patricia (Symposium on Usable Security and Privacy (USEC) 2025)
To facilitate the growing demand for a universal means of digital identification across services, while preserving user control and privacy, multiple digital identity implementations have emerged. From a technical perspective, many of these rely on established concepts within cryptography, allowing them to provide benefits in terms of security and privacy. Recent legislation also promises broader recognition and acceptance of digital identities, both in the digital world and beyond. However, research into the usability, accessibility, and user understanding of digital identities is rare. We argue that the development of usable digital identity wallets is vital to the successful and inclusive application of digital identities in society. In this vision paper, we describe our research plans for obtaining a better understanding of how to develop these usable digital identities wallets.

SPDC single-photon source in Ti-indiffused diced ridge LiNbO3 waveguides - Kießler, Christian; Kirsch, Michelle; Lengeling, Sebastian; Herrmann, Harald; Silberhorn, Christine (Optics Continuum)
Stable and bright single photon sources are key components for future quantum applications. A simple fabrication method is an important requirement for such sources. Here, we present a single photon source based on diced ridge waveguides in titanium indiffused LiNbO 3 . These waveguides can be easily fabricated by combining planar titanium in-diffusion without lithographic patterning and easy-to-handle precision dicing. Such devices have the potential to generate high single photon rates because ridge structures are typically less prone to the photorefractive effect. We achieve waveguide propagation losses <0.4dBcm and a SHG conversion efficiency of about 81%Wcm 2 . Harnessing a type-0 SPDC process to generate 1550 nm photons, we obtain a SPDC brightness of 3⋅10 5 1s⋅mW⋅nm, with a heralding efficiency of η h =45% ( η h,wg =77.5% for the waveguide itself excluded setup losses) and a heralded second-order correlation function of g h 2 (0)<0.003 at low pump powers.

Cost-effective repair solution for twin-roll-caster rollers - Lauth, Martin; Hoyer, Kay-Peter; Schaper, Mirko; Gräfen, Winfried (Materials Research Proceedings)
Abstract. Twin-Roll-Casting (TRC) is an energy- and cost-efficient process to produce near-net-shape aluminum strips. Due to the high affinity of molten aluminum to steel surfaces, those rollers show signs of wear throughout the rolling campaign. This leads to the necessity of restoring the worn surfaces to suitable parameters. The easiest way is to grind the surface till all superficial defects are omitted. However, the thickness of the roller is not endless, therefore the rollers must be replaced after a certain amount of surface reconditioning. This ultimately leads to the non-usability of the roller. This research shows a route to recondition the surface including the possibility of renewing worn-down surfaces with an energy- and cost-efficient high-velocity oxygen fuel (HVOF) treatment with subsequent grinding to the desired initial surface parameters.

Erzählen von Europa - Fluchtmigration in den Romanen "Das Kontingent", "Havarie" und "Gehen, ging, gegangen" - Müller, Inez (Deutsche Griechenland-Diskurse und Griechisch-Deutscher Kulturtransfer)
Keywords: Flucht; illegale Fluchthilfe; Humanität

Bewegung, Spiel und Sport im Ganztag an Grundschulen – Eine qualitative Interviewstudie zur Perspektive von pädagogischem Personal und Kindern Movement, play and sport in all-day primary schools—a qualitative interview study from the perspective of pedagogical staff and children - Noetzel, Ida; Kaufmann, Nils; Neuber, Nils; von Plettenberg, Elisabeth; Satzinger, Nicole; Schröder, Stefan; Süßenbach, Jessica; Kehne, Miriam (Forum Kinder- und Jugendsport)
Zusammenfassung Kinder verbringen zunehmend mehr Zeit in öffentlichen Bildungseinrichtungen. Eine zentrale Bildungsinstitution ist die Ganztagsgrundschule. Die dortige Planung und Umsetzung von Bewegung und Sport ist bisher nur punktuell beforscht. Es mangelt unter anderem an Befunden aus der Sicht der verschiedenen Akteur*innen sowie an Kenntnissen zur bewegungsbezogenen Qualifikation des Personals. Im Rahmen der vorliegenden Teilstudie des Projektes „Move For Health“ werden diese Desiderate aufgegriffen. Die Untersuchung erfolgte mittels qualitativer Interviews an acht Ganztagsgrundschulen. Es wurden 52 Interviews mit insgesamt 140 Personen durchgeführt. Diese setzen sich aus acht Fokusgruppeninterviews mit im Ganztag tätigem Personal sowie 44 Interviews mit Kindern der dritten und vierten Klasse zusammen. Die Resultate zeigen, dass Bewegung übergreifend in unterschiedlichen Inszenierungen stattfindet und auch von den Akteur*innen als wesentlich erachtet wird. Grundsätzlich sehen alle Befragten die Relevanz von Bewegung, benennen jedoch konkrete Bedarfe und Wünsche, die sich sowohl auf Räume und Materialen als auch auf Wissen und Kompetenzen (bspw. im methodisch-didaktischen Bereich) beziehen. Kinder artikulieren im pädagogischen Spannungsfeld von Gegenwartserfüllung und Zukunftsperspektive vielfältige Bedürfnisse und Ideen zur Ausgestaltung. Dem Personal mangelt es häufig an Kompetenzen im methodisch-didaktischen Bereich oder an Wissen über das Thema Sicherheit, um die Bewegung entsprechend zu inszenieren.

Der Deutschtreff (Universität Paderborn) - Hüllweg, Julia; Blachut, Alisa (Atlas der Hochschullernwerkstätten. Ein (un-)vollständiges Kompendium.)

Towards Practicable Algorithms for Rewriting Graph Queries Beyond DL-Lite - Löhnert, Bianca; Augsten, Nikolaus; Okulmus, Cem; Ortiz, Magdalena (The Semantic Web - 22nd European Semantic Web Conference, ESWC 2025, Portoroz, Slovenia, June 1-5, 2025, Proceedings, Part I)
Despite the advantages that the virtual knowledge graph paradigm has brought to many application domains, state-of-the-art systems still do not support popular graph database management systems like Neo4j. Their query rewriting algorithms focus on languages like conjunctive queries and their unions, which were developed for relational data and are poorly suited for graph data. Moreover, they also limit the expressiveness of the ontology languages that admit rewritings, restricting them to those that enjoy the so-called FO-rewritability property. Rewritings have thus focused on the DL-Lite family of Description Logics. In this paper, we propose a technique for rewriting a family of navigational queries for a suitably tailored fragment of ELHI. Leveraging navigational features in the target query language, we can include some widely-used axiom shapes not supported by DL-Lite. We implemented a proof-of-concept prototype that rewrites into Cypher queries, and tested it on a real-world cognitive neuroscience use case with promising results.
Keywords: Ontology-based Data Access; Property Graphs; Navigational Queries